Economia criativa e a nova agenda econômica: o sentido da abordagem classificatória para um fenômeno contemporâneo - Rodrigo Campos Dilelio (Ciências Sociais Unisinos)
The economic sociology related to the multidimensional approach to social reality has allowed Brazilian researchers to have a better understanding of the establishment of new markets for the circulation of cultural goods and services. The production of these goods has led to government actions such as printing new classifications of economic activi- ties, promoting the articulation of these sectors and making available incentives (credit lines and tax benefits) targeted at their structuring. Thus, among the so-called “creative industries” there are companies based on organizational models designed for electronic business transactions, promoting new socio-economic implications and transformations in sociability. The study aims to point out empirical evidence of the occurrence of this phenomenon, taking into account the development of a new economy based on enter- prises that adopt the principle of collaboration as part of the management of creativity in the production processes.